ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DAN HARGA POKOK PENJUALAN BERDASARKAN IDENTIFIKASI BIAYA RIIL PADA TOKO DONAT & ROTI JAYNUDIN - David Andrian Hutahaean; Bethanya Maytwin Ley; Steven Permana Pasaribu; Bonita Maytwin Ley; Hamonangan Siallagan (Jurnal Akuntansi Kompetif, 2026)
The MSME culinary industry, particularly the bakery sector, faces financial management challenges due to weak production cost recording systems. This study aims to analyze the calculation of Cost of Production (HPP) and Cost of Goods Sold (HPPnj) based on the identification of actual costs at Toko Donat & Roti Jaynudin, Medan, North Sumatra. The research method used is qualitative descriptive with a case study approach, through observation techniques and direct interviews with the business owner. Data were analyzed comparatively between the traditional recording method applied by the store and the cost accounting standard (full costing). The research results show that with a production capacity of 20,000 donut units per day, the total actual production cost is Rp13,594,204, which consists of Raw Material Costs (Rp5,446,500), Direct Labor Costs (Rp3,200,000), and Factory Overhead Costs (Rp4,947,704). The cost of goods sold per unit is obtained at Rp679.71, so the COGS for 12,500 units sold is Rp8,496,379. This study found that the owner's traditional recording method ignores overhead cost components such as asset depreciation and utilities, which results in hidden costs. The application of standard cost accounting has been proven to improve the accuracy of inventory valuation and profit and loss reports, as well as serve as a basis for more optimal managerial decision-making.